(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the challenges involved in translating idiomatic expressions containing phytonyms (plant names) from English to Uzbek and vice versa. It discusses linguistic gaps, cultural symbolism, the abstract nature of idioms, and grammatical differences that make translation difficult. Using examples from both languages, the article identifies key issues in translation and proposes effective strategies to preserve semantic clarity and cultural meaning.